ARCHIVING OPTIMIZATION IN SAMSAT BOGOR CITY LINKED WITH POLICE REGULATION NOMOR 5 OF 2012 ON MOTOR VEHICLE REGISTRATION AND IDENTIFICATION - Eka Sapari; Dadang Suprijatna; Mul yadi (Fakultas Hukum Universitas Djuanda Bogor, 2017)
Regident Ranmor aiming for orderly administration, control and supervision of motor vehicles in Indonesia, facilitate investigations offense or crime, planning, operational management and traffic engineering and transport road and national development planning. Regident Ranmor include new Ranmor registration, registration of identity change Ranmor and owners, registration or registration renewal and endorsement Ranmor. In addition to these activities regident Ranmor also includes blocking Ranmor regident documents related crime, replacement and deletion of documents regident Ranmor Ranmor registration number. The research method is needed to collect the amount of material used to answer the juridical analysis. Based on the problem, the research method used in normative juridical reseacrh method that is legal conceived as norms, rules, principles or dogmas. Mechanism archiving in Samsat Bogor City related to the Police Regulatins No. 5 of 2012 on Registration and Identifications of Motor Vehicles include: (1) Acceptance of the archive, (2) Labelling aechives, (3) the Sustainer archives made by some archivist assigned to maintain and secure confidentiality archives, and (4) Depreciation archives, Obstacles in the archiving on SAMSAT Bogor city linked with police Regulation No. 5 of 2012 on Registration and Identification of Motor Vehicles include: (1) lack of understanding of the importance of archives, (2) Increase in volume archives continuous basis, (3) There has guidelines working procedures archival, (4) the use of archives by the manager or by other parties that require long periods of time, and (5) can not or difficult rediscovery archives quickly and precisely. To overcome the problems that exist in archiving in order not to harm the institution, while the steps that can be taken include: (1) Must use storage system, (2) Need for regulating lending procedures in addition to supervision / control and control right, (3) Expanding the storage space and streamline the room as well as the existing equipment, (4) facilities archives should be qualified and with the times, (5) regularly held the treatment and prevention of damage, (6) the clerk records should be eligible, (7) Including the archives in courses or educational and training of archival and use of sophisticated technology, and (8) Conducting regular depreciation and destruction of the archives has been unused.